1998
DOI: 10.1161/01.atv.18.6.908
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Repetitive Thrombus Formation in the Stenosed Canine Coronary Artery by Enoxaparin, But Not by Unfractionated Heparin

Abstract: Abstract-Experiments were designed to compare the antithrombotic efficacy of enoxaparin and unfractionated heparin (UH) in a model of platelet-dependent cyclic flow reductions (CFRs) in the stenosed canine circumflex coronary artery. Low-molecular-weight heparins (LMWHs) are safe and effective in the prevention and treatment of venous thromboembolism. The present experiments were designed to evaluate the potential use of LMWHs in arterial thrombotic indications by comparing the antithrombotic effect of an LMWH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The survival of dogs receiving enoxaparin in this cohort is comparable with the results of that in other studies where high‐dose UFH, individually adjusted UFH, clopidogrel, or ultra low dose aspirin was used as thromboprophylactic agents, and is somewhat better than the survival in dogs with IMHA who received a fixed dose of UFH . In some canine studies of experimentally induced thrombosis, enoxaparin in various dosing regimens and in combination with other anticoagulant drugs was superior to UFH in preventing thrombus formation, but further studies are needed to determine the efficacy of enoxaparin therapy compared with other anticoagulant therapies in dogs with IMHA. Laboratory testing or diagnostic imaging that might have indicated the incidence of thrombotic events in surviving dogs was not evaluated in this study.…”
Section: Discussionsupporting
confidence: 73%
“…The survival of dogs receiving enoxaparin in this cohort is comparable with the results of that in other studies where high‐dose UFH, individually adjusted UFH, clopidogrel, or ultra low dose aspirin was used as thromboprophylactic agents, and is somewhat better than the survival in dogs with IMHA who received a fixed dose of UFH . In some canine studies of experimentally induced thrombosis, enoxaparin in various dosing regimens and in combination with other anticoagulant drugs was superior to UFH in preventing thrombus formation, but further studies are needed to determine the efficacy of enoxaparin therapy compared with other anticoagulant therapies in dogs with IMHA. Laboratory testing or diagnostic imaging that might have indicated the incidence of thrombotic events in surviving dogs was not evaluated in this study.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast with UFH, LMWH has been shown to have a more predictive anticoagulant effect with only minor effects on platelet activation (26,27). Furthermore, administration of LMWH, but not UFH, prevented repetitive platelet-dependent thrombus formation in a stenosed canine coronary artery model (30). Platelet effects of other GP IIb/IIIa inhibitors with UFH or LMWH.…”
Section: Discussionmentioning
confidence: 99%
“…In a femoral arterial thrombosis model, Prosdocimi et al demonstrated that UFH was inferior to aspirin and other platelet aggregation inhibitors, albeit at a lower UFH dosage than in the other 2 studies . Although direct comparisons suggest superiority of antiplatelet agents for arterial thrombosis in dogs, multiple studies (19 LOE 3, Good, 1 LOE 3, Fair) suggest efficacy of anticoagulants including UFH, low molecular weight heparin (LMWH), and direct inhibitors of Xa and thrombin for arterial thrombosis in dogs . Of these, 1 study suggested that heparin may protect against renal arterial thrombosis following renal transplantation in dogs better than aspirin, although the clinical applicability of that study is limited.…”
Section: Pico Question: Antithrombotic Agents In Arterial Thrombosismentioning
confidence: 99%